НОВАЯ ПАРАДИГМА В ОБРАЗОВАТЕЛЬНОМ ПРОЦЕССЕ – УСПЕХ В РАЗВИТИИ КРИТИЧЕСКОГО МЫШЛЕНИЯ - Алламуратова, Г.Ж.; Алламуратова, А.Ж. (SCIENCE and SOCIETY, 2024)
The article discusses the issue of a new approach in the educational process: the development and implementation of new paradigms in the student education system. Their goal is to adapt the educational process to the individual needs of each student. The article presents modern aspects of new paradigms and their characteristics, and reveals in more detail the effectiveness of the integrative approach to teaching.
Keywords: new paradigms; critical thinking; educational process; efficiency; skills; innovation; digital literacy